REFLECTION OF THE FIRST WORLD WAR IN THE PUBLIC OPINION OF RUSSIANS (1914-1918) - Galina N. Rykun (Современная наука и инновации, 2022)
This article presents the main factors of forming public sentiment in Russian society during the First World War, traced the dynamics of their change, the relationship with the military successes of the Russian army is shown.